Konsep Penetapan Had dan Kafarat dengan Kias (Studi Komparasi Pendapat Imam Syāfiʻī dan Imam Abū Ḥanīfah) - Rosmita Rosmita; Rahmayani Lancang; Jeny Rheka; Nasaruddin Nasaruddin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This research aims to find out the opinions of Imam Syāfi'i and Imam Abū Ḥanīfah regarding the determination of had and kafarat with the problem that the researcher raises in this research, namely; first, what do Imam Syāfiʻī and Imam Abū Ḥanīfah think about determining had and kafarat with kias; and second, what is the comparative analysis of the opinions of Imam Syāfiʻī and Imam Abū Ḥanīfah regarding the determination of had and kafarat with kias. This research includes library research using a normative approach and a comparative approach. The research results show that; Firstly, Imam Syāfiʻī allows the use of kias in determining had and kafarat with the terms of rukun and kias conditions being in the determination of kias. Meanwhile, Imam Abū Ḥanīfah rejects the idea of ​​determining had and kafarat because had was established to prevent people from being afraid of committing immoral acts and kafarat was established to abort sins. The level of punishment is only Allah SWT. who knows, no allusions are allowed. Second, the similarity of opinion between Imam Syāfiʻī and Imam Abū Ḥanīfah is the use of figures of speech as legal istinbat. The difference is that Imam Abū Ḥanīfah does not use kias in matters of had and kafarat except for the crime of takzir, while Imam Syāfiʻī considers it valid to use kias in the aspect of jinayat. After reading and studying several propositions and opinions of Imam Syāfiʻī and Imam Abū Ḥanīfah, the researcher is more inclined to strengthen Imam Syāfiʻī's opinion because some of the arguments which say that the use of kias in determining had and kafarat are not permissible are weak. Meanwhile, Imam Syāfiʻī's opinion which allows kias in the determination of had and kafarat is strengthened by the argument of the words of the Prophet Muhammad. when sending Mu'āż bin Jabal to Yemen.